PENGARUH MODEL PEMBELAJARAN STAD DENGAN BANTUAN MEDIA GEOGEBRA TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Afrindah Wulandari; Lily Rohanita Hasibuan (IKIP Siliwangi, 2023)
This research aims to find out whether there is an effect of the STAD learning model with the help of Geogebra media on student learning outcomes. This research is an experimental research with a quasi-experimental design with a pretest-post test control group design. The sampling technique is purposive sampling. Population This study consisted of all students of class VIII SMP Muhammaduyah 25 Rantau Prapat. The samples in this study were class VIII-B as an experimental class using the Geogebra-assisted STAD learning model of 31 students and class VIII-A as a control class using the learning model. conventional as many as 32 students. The instrument used was a test in the form of an essay. The data analysis technique in this study used the t test especially Paired Sample T-Test. In data analysis using SPSS 22. From the results of the hypothesis analysis, the value of Sig. (2-tailed) of 0.000 <0.05. This means that there is an influence on students' mathematics learning outcomes in the material of Straight Line Equations which are taught using the STAD learning model with the help of Geogebra media and conventional learning models.